SUBSURFACE GEOLOGICAL CONDITION OF SEVERAL LAND COASTAL ZONE IN INDONESIA BASED ON THE GSSI GROUND PROBING RADAR (GPR) RECORD INTERPRETATION - Kris Budiono; Godwin Latuputty (Marine Geological Institute of Indonesia, 2008)
The GSSI Ground Penetrating radar have been used to profile the shallow depth of subsurface geology of several area of Land Coastal zone in Indonesia Analysis of a large data base of GPR profile from natural subsurface geological condition along the land coast line have allowed identification of reflection configuration that characterize this type of sub surface geological environment. In many contamination problem, the geological information of coastal area is sparse and drill-core description only gives a limited picture of the geometry of inhomogeneties. The Ground-Probing Radar (GPR) method is a promising tool for resolving changes of physical properties in subsurface geological condition at the scale of natural inhomogeneties arising from changing lithology composition. The objective of present work are to examine whether and to what extent the characteristic lithofacies of subsurface lithology can be recognised as mapable reflection pattern on ground probing radar (GPR) reflection profiles in order to gain information about the subsurface geometry of subsurface geology in coastal area. Key word: Subsurface geology, coastal zone, Ground Probing Radar Ground probing radar produksi GSSI telah dipergunakan untuk membuat penampang geologi bawah permukaan dangkal di beberapa kawasan pantai Indonesia. Analisa data dasar penampang GPR dari geologi bawah permukaan di kawasan pantai dapat memperlihatkan konfigurasi reflector yang mencerminkan jenis lingkungan geologi bawah permukaan. Dalam masalah kontaminasi, informasi geologi di daerah pantai yang dihasilkan dari pemboran inti hanya dapat memperlihatkan gambaran yang sederhana tentang geometri ketidakseragaman. Metoda ground probing radar merupakan alat bantu yang menjanjikan untuk menanggulangi masalah sifat fisik kondisi geologi bawah permukaan pada skala ketidak seragaman yang sebenarnya dari perubahan komposisi litologi. Tujuan utama dari penelitian ini adalah untuk menguji sampai sejauh mana karakteristik litofasies dari litologi bawah permukaan dapat dilihat sebagai pola refleksi yang dapat dipetakan dalam penampang GPR dengan maksud untuk mendapatkan informasi geometri geologi bawah permukaan di daerah pantai. Kata kunci: Geologi bawah permukaan, zona pantai, â€œGround probing radarâ€